Numerical analysis of the stress state of specimens made of three-dimensional reinforced composite - Osheva, Irina Yurievna (Computational Continuum Mechanics, 2011)
Numerical simulation of a compression test of the prismatic specimen made of three-dimensional reinforced composite with large-cell structure is considered. The structural-phenomenological approach is used to describe the stress state of the material. An analysis is carried out to study the effect of friction between the contacting surfaces of the prismatic element and the loading plate and the influence of the position of the reinforcing frame of the element with respect to its edges on the stress state of specimens.
Keywords: three-dimensional reinforced composite; structural-phenomenological approach; compression test; numerical simulation